2017
DOI: 10.21608/zjar.2017.53193
|View full text |Cite
|
Sign up to set email alerts
|

Response of Three Sugar Beet Varieties to Planting Density and Potassium Fertilizer Levels Under Sandy Soil Conditions

Abstract: Two field experiments were carried out at El-Khattara experimental farm, Faculty of Agriculture, Zagazig University, Sharkia Governorate, Egypt during the two successive seasons of 2011/2012 and 2012/2013. This study aimed to investigate the response of yield and quality of three multigerm sugar beet varieties (Rass Poly, Panther and Pleno) to three planting densities (28000, 33600 and 42000 plants/fad.) and three potassium fertilizer levels (0, 24 and 48 Kg K 2 O/fad.) in sandy soil under drip irrigation syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 15 publications
9
3
0
Order By: Relevance
“…On the other hand, purity and sugar lost in molasses percentages showed insignificant response to the studied planting densities. The obtained results concerning sucrose and extractable sugar percentages are in concurrence with those recorded by Hozayn et al (2013), El-Hity et al (2014) and Yasin (2017) . However Refay (2000) indicated that planting densities had no significant effect on sugar percentage of sugar beet.…”
Section: Juice Qualitysupporting
confidence: 92%
“…On the other hand, purity and sugar lost in molasses percentages showed insignificant response to the studied planting densities. The obtained results concerning sucrose and extractable sugar percentages are in concurrence with those recorded by Hozayn et al (2013), El-Hity et al (2014) and Yasin (2017) . However Refay (2000) indicated that planting densities had no significant effect on sugar percentage of sugar beet.…”
Section: Juice Qualitysupporting
confidence: 92%
“…These results may be attributed to genetic factors as well as their interactions with the environmental conditions. The results of varieties in root diameter obtained in the paest study are in agreement with those obtained by Yasin (2017) and Teama et al (2018).…”
Section: -Root Diameter (Cm)supporting
confidence: 91%
“…This increase may be due to the high competition between plants for plants growth resources. In those connection Ouda, Sohier (2005), Shalaby et al (2011) and Yasin (2017) reported that root length was increased by increasing plant spacing.…”
Section: Results and Discussion B -Yield Components: -1-root Length (Cm)mentioning
confidence: 93%
See 2 more Smart Citations